A generic approach to conference scheduling with integer programming - Pylyavskyy, Yaroslav; Jacko, Peter; Kheiri, Ahmed (European journal of operational research, 2024)
Conferences are a key aspect of communicating knowledge, and their schedule plays a vital role in meeting the expectations of participants. Given that many conferences have different constraints and objectives, different mathematical models and heuristic methods have been designed to address rather specific requirements of the conferences being studied per se. We present a penalty system that allows organisers to set up scheduling preferences for tracks and submissions regarding sessions and rooms, and regarding the utilisation of rooms within sessions. In addition, we also consider hybrid and online conferences where submissions need to be scheduled in appropriate sessions based on timezone information. A generic scheduling tool is presented that schedules tracks into sessions and rooms, and submissions into sessions by minimising the penalties subject to certain hard constraints. Two integer programming models are presented: an exact model and an extended model. Both models were tested on five real instances and on two artificial instances which required the scheduling of several hundreds of time slots. The results showed that the exact model achieved optimal solutions for all instances except for one instance which resulted in 0.001% optimality gap, and the extended model handles more complex and additional constraints for some instances. Overall, this work demonstrates the suitability of the proposed generic approach to optimise schedules for in-person, hybrid, and online conferences. •We present a generic scheduling tool for in-person, hybrid, and online conferences.•We tackle the conference scheduling problem with integer programming models.•Our models handle conferences with up to a few thousand submissions.•The models were tested on real instances.